2013
DOI: 10.1007/s00586-013-3006-z
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical fusion for radicular-disc conflict performed by three different procedures: clinical and radiographic analysis at long-term follow-up

Abstract: As shown by the obtained clinical and radiographic results, the anterior interbody fusion with stand-alone peek cage containing β-tricalcium phosphate could be considered an effective and reliable procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The present study is not the first study to use PEEK cages filled with commercially available granulated beta-TCP in an injectable form in ACDF; however, only a handful of reports were available. 15 , 29 , 30 , 31 , 32 Our results were consistent: results indicate that use of beta-TCP results in comparable fusion rates, and has the advantage of reduced morbidity associated with autogeneous grafts.…”
Section: Discussionsupporting
confidence: 76%
“…The present study is not the first study to use PEEK cages filled with commercially available granulated beta-TCP in an injectable form in ACDF; however, only a handful of reports were available. 15 , 29 , 30 , 31 , 32 Our results were consistent: results indicate that use of beta-TCP results in comparable fusion rates, and has the advantage of reduced morbidity associated with autogeneous grafts.…”
Section: Discussionsupporting
confidence: 76%
“…A total of 153 articles were assessed by two independent reviewers for eligibility and finally 17 articles -5 prospective and 12 retrospectivewere included. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The search mechanism used in the review is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Zagra et al, 59 33 patients underwent implantation of a stand-alone PEEK cage augmented with β-TCP and were compared with 2 other groups: (1) iliac autograft with plate fixation and (2) iliac graft with titanium cage. All patients achieved a solid fusion at the last follow-up.…”
Section: Tricalcium Phosphatementioning
confidence: 99%
“…Nevertheless, ACDF with PEEK cage and β-TCP was not only clinically effective but also resulted in a better fusion rate. 59 Sugawara et al 37 used cylindrical titanium cages packed with β-TCP in 57 patients and found no dislocation or material-related complications, in contrast to the study by Zagra et al 59 They reported that the fusion rate was significantly higher in the β-TCP compared with HA at 6-month (46% vs 24%) and 1-year follow-up (69% vs 49%); however, the fusion rate was similar between groups at 2-year follow-up (94% vs 90%). 37 Park and Roh 60 compared the efficacy of iliac autograft with PEEK cages filled with β-TCP.…”
Section: Tricalcium Phosphatementioning
confidence: 99%